Central African Economic and Monetary Community : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The report provides a summary of the level of compliance at the Central African Economic and Monetary Community (CEMAC) regional level and provides recommendations to improve compliance. The assessment focuses on the regional Anti-Money Laundering and Combating the Financing of Terrorism (AML-CLT) framework and its conformity with international standard. The paper reviews the institutional framework, laws, regulations, guidelines, and other requirements, and the regulatory and other systems in place to deter money laundering and the financing of terrorism through financial institutions and designated non-financial businesses (DNFBPs). It also examines the capacity, implementation, and effectiveness of all these systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet